2020
DOI: 10.2174/1573406416666200306115035
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Docking and Biological Evaluation of Novel Flavone Derivatives as Potential Anticancer Agents Targeting Akt

Abstract: Background: Flavonoids are naturally occurring compounds with versatile health-promoting effects against various diseases. Objective: To synthesize and evaluate biological activity of novel flavone derivatives against cancer. Methods: A new series of 2-hydroxy-α,β-unsaturated ketones 2a-h was synthesized via the reaction of N-substituted-indole-3-carboxaldehydes 1a-h with 2-hydroxy acetophenone in the presence of piperidine. The oxidative cyclization of 2a-h using hydrogen peroxide/KOH and/or dimethyl s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Steatosis is the earliest response to excessive drinking, which is characterized by fat deposition in liver. This phenomenon is reversible after stopping drinking, but long-term excessive drinking can lead to inflammation, fibrosis, and even cancer ( Abo-Salem et al, 2021 ; Ali et al, 2021 ; Mohamady et al, 2020 ). According to statistics, more than 90% of alcoholics show fat accumulation, and 30% of them develop severe ALD ( Gala and Vatsalya, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Steatosis is the earliest response to excessive drinking, which is characterized by fat deposition in liver. This phenomenon is reversible after stopping drinking, but long-term excessive drinking can lead to inflammation, fibrosis, and even cancer ( Abo-Salem et al, 2021 ; Ali et al, 2021 ; Mohamady et al, 2020 ). According to statistics, more than 90% of alcoholics show fat accumulation, and 30% of them develop severe ALD ( Gala and Vatsalya, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several possible key player targets in cancer that have been linked to various cancer types such as Akt, Topo-isomerase II-B, CTLA4, STAT4, FXR. 45–48 …”
Section: Discussionmentioning
confidence: 99%
“…Our data confirms a pattern that had already been suggested by the literature. Whereas flavonoids are anti-proliferative at high concentrations (Abosalem, Gibriel, Al-Awady, & Mandour, 2020;Ammendola et al, 2020) and thus have certain anti-carcinogenic properties, at lower concentrations their effect on precursor cells is more complex and appears to be activating rather than inhibitory. Indeed, we found that 25 µM quercetin increased cell cycle exit and promoted survival and differentiation of adult hippocampal precursor cells, both ex vivo and in vivo.…”
Section: Discussionmentioning
confidence: 99%